Communities of anamorphic fungi on green leaves and leaf litter of native forests of Scutia buxifolia and Celtis tala: composition, diversity, seasonality and substrate speciﬁcity - Allegrucci, Natalia (2015)
Background: Xeric forests dominated by two tree species, Scutia buxifolia (Rhamnaceae) and Celtis tala (Ulmacea), are temperate, semi-deciduous wooded communities that represent the most abundant woodlands on the eastern plains of Buenos Aires Province, Argentina. The district of Magdalena has one of the most well-preserved native-forest areas, with an environmental heterogeneity that gives rise to the wide variability in the vegetation present. Aims: The aim of this study was to analyze the species composition, diversity, seasonal variations, and substrate specificity of anamorphic fungi (Ascomycota) on the green leaves and in the leaf litter of native forests dominated by Scutia buxifolia and Celtis tala from Magdalena, Buenos Aires, Argentina. Methods: In order to obtain the mycobiota of decomposition, seasonal samples of green leaves and leaf litter from both types of trees were collected over a two-year period. In the laboratory, the leaves were placed in a moist chamber and incubated at room temperature. Results: A total of 100 species of anamorphic Ascomycota were identified in both forests. No significant variations were observed in the richness, diversity, or evenness of the fungal communities of the green leaves and leaf litter of both forests between seasons. Conclusions: The species that characterized the fungal communities in the leaves of each of the trees were found to be different. The type of substrate had a stronger influence in determining the composition of the fungal community in both types of forests.